Wetlands management in Cambodia socioeconomic, ecological and policy perspective. - Torell, M.; Salamanca, A.M.; Ratner, B.D. (eds.). (Penang, Malaysia WorldFish Center, 2004)
WorldFish Center Technical Report 64
Keywords: Wetlands; Socioeconomic aspects; Resource management; Policies; Environment management